Long-term quality of life in inoperable non-small cell lung cancer patients treated with conventionally fractionated compared to hyperfractionated accelerated radiotherapy – Results of the randomized CHARTWEL trial. Issue 2 (February 2018) - Hechtner, Marlene; Krause, Mechthild; König, Jochem; Appold, Steffen; Hornemann, Beate; Singer, Susanne; Baumann, Michael
Abstract: Background and purpose: To evaluate the quality of life (QoL) of patients with inoperable non-small cell lung cancer treated with conventionally fractionated radiotherapy (CF) vs. continuous hyperfractionated accelerated radiotherapy weekend-less (CHARTWEL). Material and methods: The largest monocentric subgroup of the phase III CHARTWEL trial was analyzed up to three years after randomization. QoL was assessed with the European Organization for Research and Treatment of Cancer QoL Core Questionnaire (QLQ-C30) and lung cancer module (QLQ-LC13) and compared using linear mixed models. QoL interrelations with recurrence, metastasis, and death were explored by multi-state modeling. Results: 160 patients (98%) provided at least one QoL assessment. Average treatment differences of CF vs. CHARTWEL over three years were −5.4 points (95%CI [−13.6, 2.8], p = 0.19) in global QoL, 11.9 ([2.8, 21.0], p = 0.01) in fatigue, 13.4 ([3.5, 23.3], p = 0.009) in pain, 10.5 ([1.3, 19.6], p = 0.03) in dyspnea, and 5.2 ([−2.7, 13.0], p = 0.19) in dysphagia. At 12 months, the probabilities of being disease-free with good, good or moderate, any global QoL, or alive were 5.1%, 20.3%, 34.2%, 54.4% under CF and 10.4%, 21.0%, 37.5%, 65.3% under CHARTWEL. Conclusions: Over three years, QoL was similar or more favorable under CHARTWEL compared to CF. Modeling QoL together with disease states provided additional insight into treatment comparisons.